Validity of short food questionnaire items to measure intake in children and adolescents: a systematic review. Issue 1 (26th August 2016) - Golley, R. K.; Bell, L. K.; Hendrie, G.A.; Rangan, A.M.; Spence, A.; McNaughton, S. A.; Carpenter, L.; Allman‐Farinelli, M.; de Silva, A.; Gill, T.; Collins, C.E.; Truby, H.; et al.
Abstract: Background: Short food questions are appealing to measure dietary intakes. Methods: A review of studies published between 2004 and 2016 was undertaken and these were included in the present study if they reported on a question or short item questionnaire (≤50 items, data presented as ≤30 food groups) measuring food intake or food‐related habits, in children (aged 6 months to 18 years), and reported question validity or reliability. Thirty studies met the inclusion criteria. Results: Most questions assessed foods or food groups ( n  = 29), with the most commonly assessed being fruit ( n  = 22) or vegetable intake ( n  = 23), dairy foods and discretionary foods ( n  = 20 studies each). Four studies assessed food habits, with the most common being breakfast and meal frequency ( n  = 4 studies). Twenty studies assessed reliability, and 25 studies determined accuracy and were most commonly compared against food records. Evaluation of question performance relied on statistical tests such as correlation. Conclusions: The present study has identified valid and reliable questions for the range of key food groups of interest to public health nutrition. Questions were more likely to be reliable than accurate, and relatively few questions were both reliable and accurate. Gaps in repeatable and valid short food questions have been identified that will provide direction for future tool development.